An Overview on Management of Psoriasis Using Calcipotriene and Its Amalgamation as Nano Based Drug Delivery System - Aayushi Tatiya; Javesh Patil; Tejasweeni Girase; Mamta Patil; Kiran Patel (Materials Proceedings, 2023)
A skin ailment known as psoriasis, which affects 2–5% of people worldwide, is characterised by excessive keratinocyte proliferation and abnormal differentiation. Calcipotriene, a synthetic vitamin D analogue, is the first-line treatment for psoriasis. It may be used in combination with methotrexate, tazarotene, acitretin, cyclosporine, and corticosteroids. It reduces the number of T cells and regulates the inflammatory response in psoriatic lesions. However, the effectiveness of pharmacotherapy based on conventional formulations for treating patients is only partially favourable. Recent developments in nanotechnology-based nanomedicines may allow us to improve the efficacy and safety of pharmacotherapeutic treatments for psoriasis. Enhancing therapeutic efficacy while lowering toxicity through overall dose reduction are two spectacular effects of using nanomedicine as a medication carrier. This novel method efficiently ensures the site-specific administration of medications throughout the skin to treat psoriatic lesions. The present manuscript aims to discuss the chemistry and pharmacology of calcipotriene, conventional pharmacotherapy and contemporary research on calcipotriene, and the combinations of it that are used as nanomedicines for the better management of psoriasis. This review primarily focuses on the nanoemulsion loaded gel of calcipotriene and clobitasol propionate as it offers high drug loading and retention in the skin, improving the local concentration of both drugs and reducing their systemic side effects. Calcipotriene and methotrexate combined in a nanostructured lipid carrier are also the most recent generation of solid lipid nanoparticles, with better drug loading, controlled release, and enhanced bioavailability.